Opioid Use in Pregnancy. Issue 6 (November 2017) - Killion, Molly M.
Abstract : In the last 10 years, opioid use has quadrupled in the United States, including increased use in pregnancy, leading to a fivefold increase neonatal abstinence syndrome. Findings of a National Institute of Child Health and Human Development workshop of experts to evaluate opioid use in pregnancy and related neonatal and childhood effects were published in July 2017. Our maternity nursing expert, Molly Killion, reviews the workshop recommendations.